UJI ORGANOLEPTIK STIK BOLU PISANG BERBAHAN BAKU HALAL - Hamdi Hamdi; Astuti Astuti (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
Bananas that are too ripe are rarely used. Processing bananas into a processed product of banana sponge sticks is one of the efforts to increase the added value of over-maturity bananas. The purpose of this study was to determine the effect of using kepok, barlin, and pisang pisang on banana sponge sticks on organoleptic. Qualitative data were obtained from the results of filling out the questionnaire by the panelists in the form of numbers and tabulated in tables. The treatments were (1) SBK1 = Kepok banana sponge sticks, (2) SBB2 = Berlin banana sponge sticks, (3) SBP3 = Banana banana sponge sticks, (4) SBK1 PSR = Kepok banana sponge sticks mixed with plantains, (5) SBB2 PSR = barlin banana sponge sticks mixed with plantains, and (6) SBP3 PSR = banana banana sponge sticks mixed with plantains. The panelist used is the consumer panelist. Conclusion: (1) Baked banana sponge sticks treated with different types of bananas are somewhat favored by consumers in terms of color, aroma, and texture parameters with almost the same level of preference. Meanwhile, from the taste parameter, the level of preference is also almost the same but with a level of preference approaching a scale of 6 (likes) from a scale of 7; (2) The most preferred baked banana sponge sticks in terms of color, aroma, taste and texture parameters based on the highest scoring ranking was pisang pisang sponge sticks (SBP3), which was also the most preferred type in terms of taste parameters (score 6.05) and texture (score 5.33) compared to all treatments.